PRE-SCHOOL EDUCATION IN THE CONDITIONS OF MODERNIZATION OF EDUCATION FORMATION OF MATHEMATICAL IDEAS IN CHILDREN THEORETICAL FOUNDATIONS OF THE METHODOLOGY - Rahmatjonzoda is the son of Ahrorjon Ahmat (Journals Park Publishing, 2023)
The article describes the theoretical foundations of the methodological features of the formation of mathematical concepts in children of preschool age.
Keywords: article, method, mathematics, imagination, child, mind, symptom, sign.